Metabolic signals in sleep regulation: the role of brown adipose tissue - Éva Szentirmai; Levente Kapás (Neurobiology of Sleep and Circadian Rhythms)
The regulation of sleep, while primarily attributed to the interplay between circadian and homeostatic processes, is significantly influenced by a multitude of additional factors that profoundly impact sleep quantity and quality. These factors encompass both external environmental stimuli, such as ambient temperature and somatosensory inputs, and internal physiological changes. The intricate relationship between metabolism and sleep has been a subject of extensive research, with particular attention given to the role of metabolic signals in sleep regulation. Among these, the brown adipose tissue (BAT) has emerged as a key player, studied from various perspectives including its physiological responses to sleep deprivation, its effects on sleep when activated, the consequences of impaired BAT thermogenesis on sleep patterns, and its metabolic activity across different sleep states. The cumulative evidence from these investigations suggests that BAT plays a crucial role in maintaining an optimal metabolic environment conducive to sleep, a function that becomes particularly significant in contexts of prior sleep loss, inflammatory conditions, and fluctuations in ambient temperature.